Idiopathic inflammatory myopathies - Lundberg, Ingrid E; Fujimoto, Manabu; Vencovsky, Jiri; Aggarwal, Rohit; Holmqvist, Marie; Christopher-Stine, Lisa; Mammen, Andrew L; Miller, Frederick W (Nature reviews. Disease primers, 2021)
Idiopathic inflammatory myopathies (IIM), also known as myositis, are a heterogeneous group of autoimmune disorders with varying clinical manifestations, treatment responses and prognoses. Muscle weakness is usually the classical clinical manifestation but other organs can be affected, including the skin, joints, lungs, heart and gastrointestinal tract, and they can even result in the predominant manifestations, supporting that IIM are systemic inflammatory disorders. Different myositis-specific auto-antibodies have been identified and, on the basis of clinical, histopathological and serological features, IIM can be classified into several subgroups - dermatomyositis (including amyopathic dermatomyositis), antisynthetase syndrome, immune-mediated necrotizing myopathy, inclusion body myositis, polymyositis and overlap myositis. The prognoses, treatment responses and organ manifestations vary among these groups, implicating different pathophysiological mechanisms in each subtype. A deeper understanding of the molecular pathways underlying the pathogenesis and identifying the auto-antigens of the immune reactions in these subgroups is crucial to improving outcomes. New, more homogeneous subgroups defined by auto-antibodies may help define disease mechanisms and will also be important in future clinical trials for the development of targeted therapies and in identifying biomarkers to guide treatment decisions for the individual patient.
Keywords: Autoimmune Diseases; Myositis; dermatomyozitida; myozitida s inkluzními tělísky; myozitida; Humans; Dermatomyositis; lidé; Muscle Weakness; Myositis, Inclusion Body; autoprotilátky; Autoantibodies; svalová slabost; autoimunitní nemoci